2021
DOI: 10.3390/su132212887
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sludge Concentration and Disintegration/Solubilization Pretreatment Methods on Increasing Anaerobic Biodegradation Efficiency and Biogas Production

Abstract: It is urgent to determine suitable municipal sludge treatment solutions to simultaneously minimize the environmental negative impacts and achieve sustainable energy benefits. In this study, different sludge pretreatment techniques were applied and investigated to enhance the sludge solubility and, subsequently, facilitate the anaerobic biodegradation performance of the mixed sludge under different sludge concentrations and pretreatment techniques. The sludge characteristics before and after pretreatment and ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
(30 reference statements)
0
7
0
1
Order By: Relevance
“…The cumulative methane yields for controls (Control-4%TS, Control-8%TS, and Control-12%TS) were 208.31 ± 1, 193.92 ± 2.3, and 157.81 ± 2 mL CH 4 /g COD (Figure ). Thus, with an increasing solids content, methane yields decreased ( p -value = 0.006), which could be related to increased sludge viscosity and mass transfer limitation at a higher solids content . The THP at 160 °C increased methane yield (Table S3) for the sample with 12% TS (THP-12%TS), indicating that the THP at a higher solids content could alleviate such a mass transfer limitation by disintegrating sludge flocks and thereby increasing the methane yield up to 62% compared to the corresponding control (Control-12%TS) (Figure S1).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The cumulative methane yields for controls (Control-4%TS, Control-8%TS, and Control-12%TS) were 208.31 ± 1, 193.92 ± 2.3, and 157.81 ± 2 mL CH 4 /g COD (Figure ). Thus, with an increasing solids content, methane yields decreased ( p -value = 0.006), which could be related to increased sludge viscosity and mass transfer limitation at a higher solids content . The THP at 160 °C increased methane yield (Table S3) for the sample with 12% TS (THP-12%TS), indicating that the THP at a higher solids content could alleviate such a mass transfer limitation by disintegrating sludge flocks and thereby increasing the methane yield up to 62% compared to the corresponding control (Control-12%TS) (Figure S1).…”
Section: Resultsmentioning
confidence: 95%
“…Thus, with an increasing solids content, methane yields decreased (p-value = 0.006), which could be related to increased sludge viscosity and mass transfer limitation at a higher solids content. 22 The THP at 160 °C increased methane yield (Table S3) for the sample with 12% TS (THP-12%TS), indicating that the THP at a higher solids content could alleviate such a mass transfer limitation by disintegrating sludge flocks 20 and thereby increasing the methane yield up to 62% compared to the corresponding control (Control-12%TS) (Figure S1). Also, the THP enhanced the methane production by ∼10% for samples with 4 and 8% TS (THP-4%TS and THP-8%TS) compared to their respective controls (Control-4%TS and Control-8%TS).…”
Section: ■ Materials and Methodsmentioning
confidence: 96%
“…También se ha demostrado que los métodos de pretratamiento, como la preparación del sustrato, la solubilización mecánica en combinación con el tratamiento térmico a baja temperatura, afectan el rendimiento del biogás. En procesos de digestión anaeróbica con lodos de aguas residuales consiguiente la aceleración de la digestión anaeróbica (Ahn & Chang, 2021). En el caso de residuos que contengan una gran cantidad de materia leñosa con un alto contenido de lignina, se requieren tiempos más largos para lograr la producción de biogás deseada.…”
Section: Discussionunclassified
“…Pretreatment, co-digestion, bioaugmentation, biohythane, temperature, organic loading rate and reactor design are some of the ways to increase biogas yield [89]. It has also been shown that pretreatment methods, such as substrate preparation, mechanical solubilisation in combination with low-temperature heat treatment, affect biogas yield in AD processes with wastewater sludge because of a higher ability to dissolve sludge and consequent acceleration of anaerobic digestion [90]. In the case of waste containing a large amount of woody matter with a high lignin content, longer times are required to achieve the desired biogas production.…”
Section: Anaerobic Digestionmentioning
confidence: 99%